The Ordinances of the City of Monterey: A Municipal Corporation of the State of California Under a Freeholder's Charter: Classified with Appendix Containing the Charter of Said City: February, 1913, at 112 (1913) - (:unkn) unknown (My University, 1892)
Ordinance No. 49-To Prohibit the Carrying of Concealed Weapons, §§ 1-3: Prohibited the wear or concealed carry of any dirk, pistol, sword-cane, slung-shot, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED